Seniors in the financial services market - Wierzbicka, Ewa (Journal of Finance and Financial Law, 2022)
The purpose of the article/hipothesis: To determine the trends of changes in the situation of seniors in the financial services market in 2018–2020. The author assesses the standard of living and economic situation of seniors in Poland. The author indicates what factors and conditions affect the activity of seniors in the financial market as well as their safety as clients of financial institutions. According to the author, seniors bear the greater risk while choosing financial products appropriate to their needs and conditions, in comparison with other consumer groups. On a larger scale, this group of consumers is also affected by the risk of mis-selling and fraud, as well as cyber risk. The above-mentioned types of risk are exacerbated by the decreasing availability of financial services that are specifically dedicated to this group of clients. Research method: Critical analysis of the literature on the subject and results of empirical research and statistical data available. Selected reports of institutions such as the Polish Banks Association, the National Bank of Poland, the Credit Information Bureau as well as reports of advisory and consulting companies were also analyzed. Research results: Indication of the basic conditions influencing the economic situation of seniors in Poland and their position as consumers of products offered by the financial intermediaries. Defining the basic determinants of seniors' safety in the financial services market. So far, Poland has not developed a system of comprehensive protection of seniors, based on intergenerational solidarity in which, alongside government and local government institutions, financial intermediaries would actively participate.